Burnout Dimensions with Work-Family Conflict among Hotel Employees: Flow Experience as Mediating Role - Mark, Kasa; Zaiton, Hassan (Global Academy of Training & Research (GATR) Enterprise, 2017)
gruelling demand of the day-to-day operations and stress will eventually lead to the burnout dimensions (exhaustion and disengagement). This may have adverse effects to their relationship with their family members. Interestingly, Malaysian’s cultural dimension – collectivism; may explain this in a rather interesting discussion. Previous studies had revealed fascinating findings of a relationship between the burnout dimensions with work-family conflict (WFC) and how flow mediates the relationship between burnout dimensions with WFC Methodology/Technique – A primary survey of 233 hotel employees in Kuching, Malaysia revealed that indeed there is a correlation between the relationships and that flow mediates the variables. Findings – The results obtained from this study suggest the importance of hotel organizations in utilizing some proactive actions to promote flow experience among their employees. This article also discloses the practical implications and provides suggestions for future research in the similar field of study. Novelty – The research provides supported suggestions for proactive action to eliminate burnout at workplace.